A Comprehensive Review on Multi-objective Optimization Techniques: Past, Present and Future - Sharma, Shubhkirti; Kumar, Vijay (Archives of computational methods in engineering, 2022)
Realistic problems typically have many conflicting objectives. Therefore, it is instinctive to look at the engineering problems as multi-objective optimization problems. This paper briefly explains the multi-objective optimization algorithms and their variants with pros and cons. Representative algorithms in each category are discussed in depth. Applications of various multi-objective algorithms in various fields of engineering are discussed. Open challenges and future directions for multi-objective algorithms are suggested. This study covers relevant aspects of multi-objective algorithms that which will help the new researchers to apply these algorithms in their research field.